2009
DOI: 10.1590/s0004-282x2009000300010
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and mild cognitive impairment in patients with Parkinson's disease

Abstract: -The objective of this research was to assess the occurrence of cognitive impairment in 32 individuals (average age: 67.2 years old) with Parkinson's disease (PD). Procedures: clinical-neurological assessment; modified Hoehn and Yahr staging scale (HYS); standard neuropsychological battery of CERAD (Consortium to Establish a Registry for Alzheimer's Disease); Pfeffer questionnaire; and Clinical Dementia Rating. A comparison was made with a control group (CG), consisting of 26 individuals with similar age and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 26 publications
(37 reference statements)
3
19
0
5
Order By: Relevance
“…29 The memory difficulties expressed in their recall deficit of the word list in this study could reflect the involvement of multiple cortical and subcortical neural pathways and not temporal-limbic involvement 4 caused by a slowing up of the information process or by impairment of evocative strategies more than a mnemic deficit as such. These mechanisms also contribute to the difficulties shown in the word list memory with repetition task, and this finding is similar to that of Tedrus et al 26 The major methodological limitation of our study was the extended period of assessments, and thus a degree of attrition in this group of elderly individuals was anticipated. Dementia might reduce the survival in patients with PD, and in some cases, patients developed dementia between the last evaluation and death, indicating that the prevalence observed is a conservative estimate.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…29 The memory difficulties expressed in their recall deficit of the word list in this study could reflect the involvement of multiple cortical and subcortical neural pathways and not temporal-limbic involvement 4 caused by a slowing up of the information process or by impairment of evocative strategies more than a mnemic deficit as such. These mechanisms also contribute to the difficulties shown in the word list memory with repetition task, and this finding is similar to that of Tedrus et al 26 The major methodological limitation of our study was the extended period of assessments, and thus a degree of attrition in this group of elderly individuals was anticipated. Dementia might reduce the survival in patients with PD, and in some cases, patients developed dementia between the last evaluation and death, indicating that the prevalence observed is a conservative estimate.…”
Section: Discussionsupporting
confidence: 87%
“…A strong association was found between the early occurrence of dementia and greater gravity of motor compromise in patients with PD compared to controls ( Table 1, panel C), as assessed by the H&Y stages, and this finding is similar to the studies previously reported from the Brazilian population. 26 Thus, compared to cognitively preserved individuals, the MMSE ratings differed significantly among patients who had PD much early in their life, thereby dementia setting in among individuals having PD for a longer duration. These individuals were found to have a more advanced clinical stage of dementia and had greater functional impairment.…”
Section: Discussionmentioning
confidence: 96%
“…The clinical manifestations of Parkinson's disease (PD) are essentially motor, but cognitive and behavioral disturbances also occur, characterizing dementia in approximately 30% of the cases 1,2 . Today the most common and well-known definition of QOL is that of the World Health Organization (WHO), which defines it as an individual' s perception of his position in life in the context of the culture and value systems in which he lives and in relation to his goals, expectations, standards, and concerns 3 .…”
mentioning
confidence: 99%
“…PD-MCI is associated with increasing age [19, 20, 22], male gender [20], and lower levels of education [23]. In addition, PD-MCI is generally associated with later onset of disease [20, 22], greater PD severity [19, 20, 22], and longer disease duration [3, 22].…”
Section: Predictors Of Mild Cognitive Impairment In Parkinson's DImentioning
confidence: 99%
“…Whilst the majority of studies have reported that nontremor features of bradykinesia, rigidity, postural instability, and gait disorder are particularly associated with cognitive dysfunction [22, 24, 25], some authors have reported that patients with tremor-dominant features are more cognitively impaired [23] and others have failed to identify any difference in motor phenotype [26]. It should be highlighted that these studies did not specifically explore the issue of PD-MCI but focused on the cognitive impairments associated with motor phenotype, although Verbaan et al (2007) gave specific consideration to the stratification of patients by their age of onset (≤50 and >50) and disease duration (≤10 years and >10 years) [22].…”
Section: Predictors Of Mild Cognitive Impairment In Parkinson's DImentioning
confidence: 99%